2022
DOI: 10.3390/en15238909
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Least Mean Square Controller for Power Quality Enhancement in Solar Photovoltaic System

Abstract: The objective of the proposed work is to develop a Maximum Power Point Tracking (MPPT) controller and inverter controller by applying the adaptive least mean square (LMS) algorithm to control the total harmonics distortion of a solar photovoltaic system. The advantage of the adaptive LMS algorithm is given by its simplicity and reduced required computational time. The adaptive LMS algorithm is applied to modify the Perturb and Observe (P&O), MPPT controller. In this controller, the adaptive LMS algorithm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The abovementioned research has made breakthrough progress in the control of PVPG, which is of There are many studies on improving the performance of power controllers and enhancing the stability of PVPG. Karchi et al [5] utilized the adaptive least mean square (LMS) algorithm to develop controllers for maximum power point tracking (MPPT) and inverter control in a solar PV system. The findings demonstrated that customizing the LMS algorithm according to the specific application can effectively control and enhance the performance of solar PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned research has made breakthrough progress in the control of PVPG, which is of There are many studies on improving the performance of power controllers and enhancing the stability of PVPG. Karchi et al [5] utilized the adaptive least mean square (LMS) algorithm to develop controllers for maximum power point tracking (MPPT) and inverter control in a solar PV system. The findings demonstrated that customizing the LMS algorithm according to the specific application can effectively control and enhance the performance of solar PV systems.…”
Section: Introductionmentioning
confidence: 99%